2020
DOI: 10.47626/1679-4435-2020-574
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for common mental disorders in health care workers in the city of Diamantina, state of Minas Gerais

Abstract: Introduction: The increased prevalence of mental health symptoms in primary care workers in recent years is a major cause of concern, and highlights the need to identify modifiable risk factors for mental health disorders in this population. Objectives: To analyze the prevalence of common mental disorders and associated factors in primary care workers in the city of Diamantina, state of Minas Gerais. Methods: This was a cross-sectional, explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(25 reference statements)
2
0
0
Order By: Relevance
“…A systematic review and meta-analysis, focusing on health professionals during the COVID-19 pandemic in Asia, 25 showed that females are more likely to have symptoms of CMDs such as anxiety, depression, insomnia and posttraumatic stress. These results are in line with other studies that evaluated professionals working in PHC, 8 ),( 9 ),( 18 ),( 19 although with PRs higher than those found in the present study. One of the possible explanations for the association between the variable “sex” and the CMDs, in many studies, is related to social characteristics in which, most of the time, females are responsible of doing household chores; many times, even the female professional is the only one responsible for housework and the family, in addition to suffering from gender inequality and lack of equity between women and men in the labor market, suffering from greater work overload and therefore in a condition that make them more susceptible to the risk of developing symptoms of CMDs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A systematic review and meta-analysis, focusing on health professionals during the COVID-19 pandemic in Asia, 25 showed that females are more likely to have symptoms of CMDs such as anxiety, depression, insomnia and posttraumatic stress. These results are in line with other studies that evaluated professionals working in PHC, 8 ),( 9 ),( 18 ),( 19 although with PRs higher than those found in the present study. One of the possible explanations for the association between the variable “sex” and the CMDs, in many studies, is related to social characteristics in which, most of the time, females are responsible of doing household chores; many times, even the female professional is the only one responsible for housework and the family, in addition to suffering from gender inequality and lack of equity between women and men in the labor market, suffering from greater work overload and therefore in a condition that make them more susceptible to the risk of developing symptoms of CMDs.…”
Section: Discussionsupporting
confidence: 93%
“…The overall prevalence of CMDs found among PHC professionals in Montes Claros was similar to that of a survey conducted in 2013, with CHA in the same municipality of Montes Claros; 18 ) and with a percentage higher than that found in a survey conducted in 2017, with primary health care professionals in the municipality of Diamantina, also in Minas Gerais; 19 in addition to that of a study conducted in a 2005 with PHC workers in 41 municipalities in the South and Northeast regions of the country. 9 …”
Section: Discussionsupporting
confidence: 81%